The Influence Of Creative Economic Development On The Tourism Attraction Of Semarang City - Indra Tri Saputra; Dina Yulia Wijaya; Syahrudin, Muhammad (Journal of Business and Management Inaba, 2024)
The tourism sector plays a key role in increasing investment, foreign exchange earnings, local revenue, and employment. The sector is also responsible for creating and expanding formal and non-formal jobs and enterprises across the country. This study is intended to determine how the influence of Creative Economy Development on Tourism Attraction of Semarang City. In this study the authors used a survey method with descriptive and associative approaches in collecting data the authors also held a questionnaire by taking the population of visitors to the creative economy of Semarang City and using sample selection through the sample random sampling method with an error rate of 10%. Based on the results of the calculations obtained from the Influence Test Results, Creative Economic Development has a significant influence on the Tourism Attraction of Semarang City